2021
DOI: 10.1021/acsaem.1c01893
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Passivation of the SnO2/Perovskite Interface and Perovskite Absorber Layer in Perovskite Solar Cells Using KF Surface Treatment

Abstract: Recently, SnO2 has been recognized as a promising electron transport layer (ETL) for perovskite solar cells (PSCs) due to its outstanding optoelectronic properties and low-temperature fabricating process. However, the detrimental defects formed at the SnO2/perovskite interface and within bulk perovskite films cause severe non-radiative recombination, limiting the further improvement of power conversion efficiencies (PCEs). Herein, we have demonstrated a facile surface treatment on SnO2 through KF modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“…The Nb 5+ spectra downshift to lower binding energy simultaneously due to the change of the chemical state. [ 41,43 ] The results indicate that hydrogen plays an important role in the activation and deactivation processes of passivation, for both the HF and RCA pretreated c‐Si.…”
Section: Resultsmentioning
confidence: 97%
“…The Nb 5+ spectra downshift to lower binding energy simultaneously due to the change of the chemical state. [ 41,43 ] The results indicate that hydrogen plays an important role in the activation and deactivation processes of passivation, for both the HF and RCA pretreated c‐Si.…”
Section: Resultsmentioning
confidence: 97%
“…[ 24 ] The lower defects intensity of Co–SnO 2 than pristine SnO 2 is better for the charge transfer and final performance of PSCs. [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
“…[24] The lower defects intensity of Co-SnO 2 than pristine SnO 2 is better for the charge transfer and final performance of PSCs. [25] To explore the crystallization of pristine SnO 2 and Co-SnO 2 ETLs, we did the morphology and crystallinity characterizations. The scanning electron microscope (SEM) images of pristine SnO 2 and Co-SnO 2 films are shown in Figure S5a-d, Supporting Information.…”
Section: Properties Of Sno 2 Etls Through Cobalt Modifyingmentioning
confidence: 99%
“…K + ions diffused into the bulk MAPbI 3 film to passivate the grain boundaries and point defects, whereas F − ions passivated the SnO 2 surface trap defects by eliminating the formation of hydroxyl groups. [284] Zuo et al introduced different functional groups onto the surface of SnO 2 by depositing various self-assembly monolayers (SAMs), which formed different chemical interactions with the perovskite film. [285] Later in 2020, Yan et al reported a choline chloride SAM on the surface of SnO 2 , which acted as a passivation layer.…”
Section: The Role Of Etl In the Performance Of Planar N-i-p Structure...mentioning
confidence: 99%
“…K + ions diffused into the bulk MAPbI 3 film to passivate the grain boundaries and point defects, whereas F − ions passivated the SnO 2 surface trap defects by eliminating the formation of hydroxyl groups. [ 284 ]…”
Section: Common Solar Cell Structures and Their Effect On Performancementioning
confidence: 99%